If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying K + -16 = 2 Reorder the terms: -16 + K = 2 Solving -16 + K = 2 Solving for variable 'K'. Move all terms containing K to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + K = 2 + 16 Combine like terms: -16 + 16 = 0 0 + K = 2 + 16 K = 2 + 16 Combine like terms: 2 + 16 = 18 K = 18 Simplifying K = 18
| 2(x+3)+7=9 | | R+R^2=24 | | (3m+8)3+m= | | X^2-31x-30=0 | | 2(9x-1)=-3(5-9x)+2 | | 3n-5=7n+12 | | 2x^2*3y= | | e/0.6-9=16 | | (0)=-14x+7 | | 6(7x+2)=42x+12 | | 6x+8x-57=95-5x | | 5=bx+c | | -14x^0+46x-12=0 | | 10-2u=4 | | 4c-5=3c | | (9+m)2m= | | 0.07(6t-5)=0.42(t-3)+0.91 | | 8a^2+32a=40 | | 2cot^4x-6cot^2x+4=0 | | v-(-7)=-10 | | 6x^2+31x+5=(6x-1) | | 4x+7(-3x+11)=-127 | | 0.4x-1.7=1.1x+2.5 | | 10x-8=5x+16 | | 0.16(y-4)+0.18y=0.14y-0.7 | | 3x*7=252 | | M^2=x+94 | | (0)=2x+24 | | -2(5.25+6.2x)=4(-3.1+2.68)x | | 5p+5=4p+7 | | 5a+6b=12c | | 13.5=-0.5a |